Cantinflas - Imperioli, Michael 1966-; Imperioli, Michael 1966-; Salas, Ilse; Méndez, Luis Gerardo; Garza, Gabriela de la; Jaenada, Óscar 1975- (Divisa Home Video, 2016)
From his humble origins on the small stage to the bright lights of Hollywood, the comedian Cantinflas became famous around the world, one joke at a time
México, 2014
Keywords: Cantinflas / 1911-1993 / Teatro; Cantinflas / 1911-1993 / Drama; Cantinflas / 1911-1993; Cantinflas -- 1911-1993; Discos videos digitales; Cómicos / México / Teatro; Grabaciones vídeo para los de audición disminuida; Películas cinematográficas populares; Comedians / Mexico / Drama; Actors / Mexico / Drama; Motion picture industry / Mexico / Drama; Cómicos / México / Drama; Actores / México / Drama; Industria cinematográfica / México / Drama; Actors; Comedians; Motion picture industry; Mexico; Mexiko; Film; DVD-Video